1991
DOI: 10.1557/proc-251-325
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hot Isostatically Pressed Bi–Sr–Ca–Cu–O as a Function of Consolidation Variables

Abstract: Fully dense, bulk Bi2Sr1.7CaCu2Ox (2212) superconductor pellets were made by hot isostatic pressing in an inert atmosphere. Electron microscopy revealed that rotation and bending of the platelike 2212 grains were responsible for much of the densification. Under processing conditions of 825°C and 105 MPa, dense pellets were obtained in 15 min. Many dislocations, planar faults, and, perhaps, intergrowths of the Bi2Sr2CuOx phase were produced during pressing. The dislocations were largely present in subgrain boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The effect of mechanical deformation and HIPing (Goretta et al, 1992c) on the development of microstructure has been studied for BSCCO 2212 to gain insight into the thermomechanical processing steps required for fabrication of wires and tapes. The microstructure evolves from a loose packing of powders to a fully dense structure within 15 min of HIPing at 825"C. Samples deformed at high temperature m_der compression have shown that strain is accommodated by a combination of dislocation glide and microcracking.…”
Section: B(t)mentioning
confidence: 99%
“…The effect of mechanical deformation and HIPing (Goretta et al, 1992c) on the development of microstructure has been studied for BSCCO 2212 to gain insight into the thermomechanical processing steps required for fabrication of wires and tapes. The microstructure evolves from a loose packing of powders to a fully dense structure within 15 min of HIPing at 825"C. Samples deformed at high temperature m_der compression have shown that strain is accommodated by a combination of dislocation glide and microcracking.…”
Section: B(t)mentioning
confidence: 99%